Return of Thoroughbred Racing Horses to the Races after Treating Slab Fractures of the Third Carpal Bone with PRP and Stem Cells - Louzada, Janaina Godinho; Botteon, Paulo de Tarso Landgraf; Figueiredo, Luciana Rodrigues de Almeida; Neto, Hélio Cunha de Menezes; Marques, Adiléa Cavalcanti; Pimentel, Aline Lucas; Kowal, Rosalie Joslin; Vieira, Juliana Braga (Acta Scientiae Veterinariae, 2021)
Background: Despite the fact that slab fracture of the third carpal bone is an event of great worldwide relevance in racehorses, the third carpal fracture doesn’t have data on treatments and return to racing in Brazil. The search for efficient treatments and which provide recovery providing horses return to racing is an objective of sports equine medicine. Regenerative therapies like Platelet Rich Plasma (PRP) and Stem Cells (MSc) have demonstrated a great potential in the treatment of several injuries. For the treatment of three Thoroughbred racing horses at Brazilian Jockey Club, with sagittal plane slab fractures of the third carpal bone, we used the association of PRP and Stem Cells for reduction of the rest and good return to conditions athletics of these horses. Cases: Three Thoroughbred racing horses, males, 4 and 5 years old, showed slab fracture third carpal bone in different moments of their activity at Brazilian Jockey Club. Usually, the treatment for this type of fracture is the arthroscopic repair and the conservative management. We performed after initial radiographic evaluation dorsoproximal-dorsodistal oblique (DPr-DDiO) “skyline”, intra-articular applications of PRP and MSCs. The treatments were performed according to the radiographic follow-up of the lesion evolution. No other treatment was performed concomitantly with cell therapy in the 3 treated patients. Three treatments were performed in the first patient and 2 in the second and third patients. Before each treatment for all patients, we performed radiography dorsoproximal-dorsodistal oblique (DPr-DDiO) ‘skyline’ of the carpus. After this step, the animal was sedated with 10% xylazine hydrochloride at a dose of 0.5 mg/kg intravenously. Antisepsis of the carpus was performed and applied with radiographic monitoring of the needle positioning, first the PRP in the volume of 2 mL and in sequence, 20 million cells MSCs suspended in autologous plasma from the cell bank of the Cellen veterinary stem cell laboratory, totalizing 4 mL. The 3 horses returned to their training routines and continued to be monitored by clinical examinations and radiography, there were no post-treatment complications and all ran again in the median time of 253 days after the first application of PRP and stem cells. Everyone won the first race after treatment. Discussion: The 3 patients suffered the fractures after running at the Brazilian Jockey Club. All fractures were simple- no comminuted slab fractures of the third carpal. In our study, we chose to carry out the treatments with PRP and MSCs by intra-articular application. The regenerative medicine occupies a prominent place in recovery from injuries and the association of PRP and MSCs have played an important role in the treatment of athlete horses in tendons, bones and joint injuries and our work, the treatment was effective, without complications, helped to reduce local inflammation, perceptually reducing the pain observed before the application and the animals started running again with a quality equivalent to that observed before the occurrence of injuries. This way, our results demonstrated that the association PRP and MSCs was effective in recovering the 3 patients, all of them ran after injury. The median time for racing was 253 days and the horses won their first races after fractures occurred. These results encourage the use of the association of PRP and MSCs also for no comminuted sagittal plane slab fractures of the third carpal in Thoroughbred Racing horses.